The Challenges of Permanence and Success in EJA-EPT at IFG in the Context of Emergency Remote Education (London Journal of Research In Humanities and Social Sciences, 2024)
This chapter aims to analyse the challenges of permanence and successfaced by students in Youth and AdultEducation integrated with VocationalEducation at the Federal Institute of Gois in the context of the Covid-19 pandemic, when the EmergencyEducation System wasadopteddue to social isolation. Methodologically, the studyis qualitative and quantitative, and the data analysedispart of a surveycarried out by the Observatory of the Brazilian Welfare State in partnership with the IFG'sObservatory of the World of Work, usinginformationgatheredfrom EJA-EPT students at the Federal Institute of Gois. The studyprofiled the EJA studentpopulation at the institution, pointing out thatthispopulation has beenseverelyimpacted by the effects of the Covid-19 pandemic. The institutionaleffortwasimportant in terms of guaranteeing the conditions of permanenceduring the term of the SEE, with evenhigher rates compared to the periodimmediatelybefore the healthcrisis. However, althoughsuccess rates, understood as approval, were considered high, the studypointed out that the objective conditions of the teaching and learning processdid not satisfactorilyfulfil the conditions for acquiring the knowledgeprovided for in the coursecurricula.
Keywords: morality.; will; greed; Dependence; freedom; necessity; fate; fatalism; moral goodnefreedom; moral goodness; choice.ss; choice.; Psychosocial Risks; Operational Distress; Employees; Public and Private Organisations; politics; ideology; Religion; theology; social activity; Church.; COVID19; Permanence and success; SEE; EJA-EPT; Emergency Remote Education